Transformation of the Russian economic model in the context of a changing world structure: prerequisites and principles - D. A. Zaitsev; Yu. V. Zvorykina; O. M. Pisareva (Вестник университета)
In the conditions of rapid qualitative changes in socio-economic relations in the Russian society and cardinal transformation of the world structure, the authors set the goal to present a conceptual approach and theoretical foundations of the national economy model transformation. The methods of content and logical analysis, as well as general scientific methods of abstraction, generalization, and synthesis were used in the problem formulation within the framework of historical and systemic approach to studying complex issues and challenges characteristic of socio-economic formations development transitional periods. The political and economic aspects of the influence of the world structure transformation on the tasks and foundations of the national state economic mechanism adaptation have been considered. The interrelation of the social structure evolution and the increasing role of national wealth effective management to ensure sovereign development and increase public welfare has been outlined. The preconditions have been analyzed and the necessity of updating the modern nation-state economic model substantiated, as well as the conceptual provisions and basic principles of updating the economic model formulated. Possible ensuring solutions in the sphere of public power, including improving the mechanism of state control over the effective use of national assets for implementing the justice principle in the economic relations system have been defined.